What happens when one picks up the Greek text? - J. G. van der Watt (Acta Theologica)
A few issues of hermeneutic nature related to Bible translation are considered. It is argued that the chosen philosophical framework (for instance, a modernist or postmodern approach) determines the way in which any process of translation is approached. Attention then shifts to some of the presuppositions and assumptions of literal translations. These presuppositions are discussed critically. Another factor determining the nature of a translation is the intended function of that particular translation. If, for instance, the intended function is to be understandable for ordinary, present-day readers, a meaning-orientated translation would be preferable. Lastly, the role of interpretation in the translation process is considered. The assumption that no interpretation takes place in the case of word-for word translations is critiqued.